Metode Demonstrasi Memandikan Jenazah dalam Pembelajaran PAI di SMAN 1 Tigo Nagari Kabupaten Pasaman - Nursi Nursalima; Charles Charles; Deswalantri Deswalantri; Wedra Aprison (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2023)
There are 4 parts to the material for managing the corpse, namely bathing, praying, shrouding and burying, but the teacher only practices one material. So that students really understand other material which is often neglected about washing the bodies, so that problems are still found related to the use of the demonstration method of washing the bodies in PAI learning. This can be seen from the condition of students who pay less attention than chatting with friends, joking and some even doing assignments other than PAI, as well as students who often go in and out of class when the teacher explains the material. The purpose of this research was to see how the teacher used the demonstration method of washing the bodies in PAI learning for students. To find out the teacher's way of dealing with problems that arise in the demonstration method of washing the bodies in PAI learning, qualitative research is the right thing. The data needed in this study is in the form of actions taken by the teacher in overcoming the problems experienced by students in the demonstration method of washing the bodies in PAI learning using interviews and observations. Because this research looks at the teacher's method, the teacher himself cannot be left behind as the main informant and students as supporting informants. After the data is collected, the researcher performs data processing and data analysis. Data reduction, data presentation and data verification are techniques that researchers use to analyze data. Furthermore, the technique of guaranteeing the validity of the data or triangulation is carried out. The triangulation that researchers use is source triangulation and technical triangulation. Demonstration Method of Bathing the Dead in PAI Learning at SMAN 1 Tigo Nagari, Pasaman Regency. It can be seen from the results of observations and interviews with PAI teachers and class XI students majoring in social studies. In this method the teacher usually explains the material first, then the teacher asks whether the students understand what I explain or not, the teacher asks the students to ask, the stage before starting the demonstration method: Create a calming atmosphere by avoiding stressful situations Make sure students observe demonstrations, pay attention to reactions all students. Providing opportunities for students to actively reflect on what they saw in the demonstration process lesson paying attention to students about the next stage. The teacher also does ice breaking so as not to be tense during the learning process and the teacher also provides motivation and prizes.